Proteomic De-Regulation in Cyanobacteria in Response to Abiotic Stresses - Babele, Piyoosh Kumar; Kumar, Jay; Chaturvedi, Venkatesh (Frontiers in Microbiology, 2019)
Cyanobacteria are oxygenic photoautotrophs, exhibiting a cosmopolitan distribution in almost all possible environments and are significantly responsible for half of the global net primary productivity. They are well adapted to the diverse environments including harsh conditions by evolving a range of fascinating repertoires of unique biomolecules and secondary metabolites to support their growth and survival. These phototrophs are proved as excellent models for unraveling the mysteries of basic biochemical and physiological processes taking place in higher plants. Several known species of cyanobacteria have tremendous biotechnological applications in diverse fields such as biofuels, biopolymers, secondary metabolites and much more. Due to their potential biotechnological and commercial applications in various fields, there is an imperative need to engineer robust cyanobacteria in such a way that they can tolerate and acclimatize to ever-changing environmental conditions. Adaptations to stress are mainly governed by a precise gene regulation pathways resulting in the expression of novel protein/enzymes and metabolites. Despite the demand, till date few proteins/enzymes have been identified which play a potential role in improving tolerance against abiotic stresses. Therefore it is utmost important to study environmental stress responses related to post-genomic investigations, including proteomics changes employing advanced proteomics, synthetic and structural biology workflows. In this respect, the study of stress proteomics offers exclusive advantages to scientists working on these aspects. Advancements on these fields could be helpful in dissecting, characterization and manipulation of physiological and metabolic systems of cyanobacteria to understand the stress induced proteomic response. Till date, it remains ambiguous how cyanobacteria perceive changes in the ambient environment that lead to the stress-induced proteins thus metabolic deregulation. This review briefly describes the current major findings in the fields of proteome research on the cyanobacteria under various abiotic stresses. These findings may improve and advance the information on the role of different class of proteins associated with the mechanism(s) of stress mitigation in cyanobacteria under harsh environmental conditions.